Computer Aided Design of Polygalacturonase II from Aspergillus niger - Noorbatcha, Ibrahim Ali; Ismail, Nur Izzah; Mohd. Salleh, Hamzah (2011)
Pectin is a complex polysaccharide found in the cell walls of plants and consisting mainly of esterified D-galacturonic acid resides in α-(1-4) chain. In production of fruit juice, pectin contributes to fruit juice viscosity, thereby reducing the juice production and increasing the filtration time. Polygalacturonase improves the juice production process by rapid degradation of pectin. In this project we have designed a novel polygalacturonase enzyme using computer aided design approaches. The three dimension structure of polygalacturonase is first modeled on the basis of the known crystal structure. The active site in this enzyme is identified by manual and automated docking methods. Lamarckian genetic algorithm is used for automated docking andthe active site is validated by comparing with existing experimental data. This is followed by in silico mutations of the enzymes and the automated docking process is repeated using the mutant enzymes. The strength of the binding of the ligands inside the active site is evaluated by computing the binding score using Potential Mean Force (PMF) method. The mutations R256Q, K258N and E252A show improvement of the binding score while N186E reduces the binding strength. The R256Q, K258N or E252A mutant enzymes can be used in the fruit juice industry to minimize the cost of juice production